Digital interprofessional communication with families in a cardiac surgery unit: insights from the pandemic - Pozzoli, Alberto; Zurfluh, Chantal; Schulz, Peter; Bianchi, Monica; Giuffrida, Silvia; Crivelli, Diego; Torre, Tiziano; Ferrari, Enrico; Demertzis, Stefanos (Frontiers in Cardiovascular Medicine, 2023)
Background The COVID-19 pandemic entailed cutting off the usual access to hospitals, denying patients daily visits from their relatives and friends. The standard communication between medical staff and relatives also suffered, with a perceived negative impact on overall care. We developed an electronic communication solution to re-establish a proactive daily communication with patients' families. Methods The communication software allowed families to receive daily inter-professional (medical, nursing and physiotherapy) updates by text message, o122n patients' postoperative clinical state. Appreciation and performance of this communication was evaluated through a prospective randomized study. Two groups were compared (group D, 32 patients “Digital” receiving daily SMS and group S, 16 patients “Standard” without SMS), assessing satisfaction through dedicated surveys under COVID-19 restrictions. Moreover, private outgoing vs incoming communication flow between patients and their relatives (phone calls and text messages, for both groups) were analysed at different timeframes of the post-operative hospital stay. Results Mean age of the population was 66 ± 7 years for both groups. The digital communication service was successfully adopted in group D in all cases, sending overall 155 communications (4.84 per patient). Calls received from relatives were 13 in group D vs 22 in group S (0.4 vs 1.4 calls per patient, p=0.002). Patients’ outgoing vs incoming traffic flow was equal in the two groups for every timeframe (first two post-op days vs the rest), independently from digital communication. Comparing satisfaction of communication (from 1 to 7), level of information and understandability resulted 6.7 in group D vs 5.6 in group S (p=0.004). Appreciation of digital communication was highest during the first three post-operative days. Conclusion The restrictions caused by the COVID-19 pandemic generated simple and highly effective ideas on digital solutions for interprofessional communication by our cardiac surgery unit. Offering this digital update service, which complements rather than replaces the classic communication method, eased the urgent need of the families for quality information, especially in the acute postoperative phase, and significantly enhanced overall satisfaction of patients and families.